2021
DOI: 10.1021/acs.macromol.0c02574
|View full text |Cite
|
Sign up to set email alerts
|

Why Enhanced Subnanosecond Relaxations Are Important for Toughness in Polymer Glasses

Abstract: This manuscript explores the connection between the fast relaxation processes in an undeformed polymer glass and essential trends in the mechanical toughness, a nonlinear mechanical property that is of practical interest for engineering polymers with high impact strength. We quantify the time scale of the molecular relaxations in the subnanosecond regime for a quiescent polycarbonate glass using inelastic and quasi-elastic neutron scattering and then correlate these processes with the macroscopic brittle-to-du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 61 publications
1
9
0
Order By: Relevance
“…Since the MFC and ρ e are different between the two polymers, the raw values of MSD are not a good metric to compare the relaxation processes of the two polymers; however, MSD is a good metric to illustrate enhanced chain mobility in response to different impact conditions. Notably, the MSD for both polymers increases with increasing V i (and E p *), indicating a connection between chain mobility and toughness that has been recently observed experimentally. , Due to a high ρ e , PE initially has a low MSD that continuously increases with V i . PS has an initial increase in MSD up to 1.5 km s –1 , after which an elbow in the data is observed and the MSD increases at a slower rate, suggesting that as the temperature increases with increasing V i , the MFC is reduced and chain mobility is enhanced.…”
supporting
confidence: 70%
See 1 more Smart Citation
“…Since the MFC and ρ e are different between the two polymers, the raw values of MSD are not a good metric to compare the relaxation processes of the two polymers; however, MSD is a good metric to illustrate enhanced chain mobility in response to different impact conditions. Notably, the MSD for both polymers increases with increasing V i (and E p *), indicating a connection between chain mobility and toughness that has been recently observed experimentally. , Due to a high ρ e , PE initially has a low MSD that continuously increases with V i . PS has an initial increase in MSD up to 1.5 km s –1 , after which an elbow in the data is observed and the MSD increases at a slower rate, suggesting that as the temperature increases with increasing V i , the MFC is reduced and chain mobility is enhanced.…”
supporting
confidence: 70%
“…Notably, the MSD for both polymers increases with increasing V i (and E p *), indicating a connection between chain mobility and toughness that has been recently observed experimentally. 27,28 Due to a high ρ e , PE initially has a low MSD that continuously increases with V i . PS has an initial increase in MSD up to 1.5 km s −1 , after which an elbow in the data is observed and the MSD increases at a slower rate, suggesting that as the temperature increases with increasing V i , the MFC is reduced and chain mobility is enhanced.…”
mentioning
confidence: 99%
“…If τ e were to become greater than the impact event, then relaxations would not engage the entanglements, and the influence of ν e during HVI would not be significant. Even if the entanglements play a role in HVI (although small), the literature reports have shown that polycarbonate displays a fast collective relaxation process, ∼10 –12 s involving a few monomeric segments . HVI testing at different molecular weights, particularly at low molecular weights, would be needed to validate if ν e has any significant contribution.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Flexibility introduced by D400 increases mobility and reduces density as well as mechanical properties of the DGEBA+D400 system 53 . A quantitative comparison of 〈𝑢 〉 between simulations and future experiments should be done with caution, since in experiments 〈𝑢 〉 is extracted from the neutron scattering intensity 60 , can depend on the scattering wavelength Q and the very definition of Debye-Waller Factor includes the whole exponential term 𝐷𝑊𝐹 = 𝑒𝑥𝑝(− 〈 〉 ), while it is customary for molecular simulation studies to use the term 𝐷𝑊𝐹 as a definition of the 〈𝑢 〉 value extracted from MSD functions 61 .…”
Section: Resultsmentioning
confidence: 99%